Enriquecimento ambiental e a modulação da emocionalidade, cuidado materno e metilação de genes em camundongos fêmeas LG/J - Rosa, Natalia Marques (Universidade Federal de São Carlos, 2022)
Environmental Enrichment (EE) can be considered as a set of environmental changes that can adjust the model of a species and favor well-being in captive animals. The present study intends to investigate the influence of EE (cardboard roll) on behavioral and epigenetic modulations in murine females of the LG/J strain in different life stages. For this, four groups were determined: group 1, positive control – continuous EE; group 2, negative control – EE absent; group 3 – EE in the pubertal phase (3 and 4 weeks of age); and group 4 – EE in the maternal phase. The emotionality of all females was evaluated by the Open Field, Elevated Plus Maze and Forced Swim tests. The mother's performance was also evaluated in terms of maternal posture (litter size, nest construction, puppies weight, placentophagy and aggressiveness against intruders) and in the Puppies Recovery Test (self grooming and mother-puppies interaction by licking, nursing and litter rescue time). Females seem, in general, to naturally present anxious and depressive behavior that intensified in later life stages. However, the use of environmental enrichment seems to mitigate these behavioral responses. Likewise, exposing females to enrichment only in the pubertal phase seems to have reflected in anxious and depressive-like behaviors in the later phase (post-weaning). The enrichment in the maternal phase promoted improvements in the posture of the females, in which the litters suffered less loss of puppies, the nests built were taller and warmer, and the puppies had more protection by the mothers in the analysis of aggression against intruders and in the rescue test. After the phenotypic analyses, it was possible to sequence a hypothalamus sample using the pocket sequencer, Oxford Nanopore MinION, which allowed learning methodologies of a fourth generation sequencing technology. Our results allowed the enrichment of discussions in the research area and support new work by our group, in the search for epigenetic markers associated with animal welfare.
Environmental enrichment and the modulation of emotionality, maternal care and gene methylation in female LG/J mice
Keywords: Bem-estar animal; Ansiedade; Depressão; Comportamento materno; Epigenética; Animal welfare; Anxiety; Depression; Maternal behavior; Epigenetics; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL